The Role of the Dorsolateral Prefrontal Cortex for Speech and Language Processing - Hertrich, Ingo; Dietrich, Susanne; Blum, Corinna; Ackermann, Hermann (Frontiers in Human Neuroscience, 2021)
This review summarizes various functions of the dorsolateral prefrontal cortex (DLPFC) that are related to language processing. To these ends, its connectivity with the left-dominant perisylvian language network was considered, as well as its interaction with other functional networks that, directly or indirectly, contribute to language processing. Language-related functions of the DLPFC comprise various aspects of pragmatic processing such as discourse management, integration of prosody, interpretation of nonliteral meanings, inference making, ambiguity resolution, and error repair. Neurophysiologically, the DLPFC seems to be a key region for implementing functional connectivity between the language network and other functional networks, including cortico-cortical as well as subcortical circuits. Considering clinical aspects, damage to the DLPFC causes psychiatric communication deficits rather than typical aphasic language syndromes. Although the number of well-controlled studies on DLPFC language functions is still limited, the DLPFC might be an important target region for the treatment of pragmatic language disorders.